Performance assessment of k2 crews in flatwater sprint kayak: a pilot study - Romagnoli, C.; Lanotte, N.; Boatto, P.; Delgado, D.; Caprioli, L.; Bonaiuto, V.; Annino, G. (VIII Congreso Internacional De Entrenadores De Piragüismo en Aguas Tranquilas, 2022)
In flatwater sprint kayaking, an effective paddling technique together with good physical performance and a smart race strategy plays a significant role among elite athletes (Baker, 2012; Michael et al., 2009). However, in order to evaluate both technical and performance improvements, coaches and athletes have relied on sports technology and the use of new devices that monitor the paddler's performance. In fact, in recent years, several devices suited for the flatwater sprint kayak sport applications have been proposed in the literature or have been made available on the market (Bonaiuto et al., 2020; Gomes et al., 2015; Sturm, 2012) while others seem to be slightly bulky and their use could affect the paddler movements (Kong et al., 2020; Pelham et al., 1993; Vos et al., 1974).